Unambiguous Intracellular Localization and Quantification of a Potent Iridium Anticancer Compound by Correlative 3D Cryo X‐Ray Imaging. (12th December 2019) - Conesa, José Javier; Carrasco, Ana C.; Rodríguez‐Fanjul, Vanessa; Yang, Yang; Carrascosa, José L.; Cloetens, Peter; Pereiro, Eva; Pizarro, Ana M.
Abstract: The iridium half‐sandwich complex [Ir(η 5 :κ 1 ‐C5 Me4 CH2 py)(2‐phenylpyridine)]PF6 is highly cytotoxic: 15–250× more potent than clinically used cisplatin in several cancer cell lines. We have developed a correlative 3D cryo X‐ray imaging approach to specifically localize and quantify iridium within the whole hydrated cell at nanometer resolution. By means of cryo soft X‐ray tomography (cryo‐SXT), which provides the cellular ultrastructure at 50 nm resolution, and cryo hard X‐ray fluorescence tomography (cryo‐XRF), which provides the elemental sensitivity with a 70 nm step size, we have located the iridium anticancer agent exclusively in the mitochondria. Our methodology provides unique information on the intracellular fate of the metallodrug, without chemical fixation, labeling, or mechanical manipulation of the cells. This cryo‐3D correlative imaging method can be applied to a number of biochemical processes for specific elemental localization within the native cellular landscape. Abstract : Das Ir gewinnt : Der Iridium‐Halbsandwich‐Komplex [Ir(η 5 :κ 1 ‐C5 Me4 CH2 py)(2‐Phenylpyridin)]PF6 ist außergewöhnlich wirksam in einer Vielzahl an Krebszelllinien. Durch Nutzung von 3D‐Kryo‐Weichstrahl‐ und Fluoreszenz‐Tomographie an derselben kryokonservierten Zelle konnte der neue Antikrebs‐Wirkstoff eindeutig und ausschließlich in den Zell‐Mitochondrien lokalisiert und quantifiziert werden.